Post flywheel squat vs. flywheel deadlift potentiation of lower limb isokinetic peak torques in male athletes - Beato, M.; de Keijzer, K. L.; Fleming, A.; Coates, A.; La Spina, O.; Coratella, G.; McErlain-Naylor, S. A. (Sports Biomechanics, 2023)
The present study investigated the post-activation performance enhancement (PAPE) of isokinetic quadriceps and hamstrings torque after flywheel (FW)-squat vs. FW-deadlift in comparison to a control condition. Fifteen male athletes were enrolled in this randomised, crossover study. Each protocol consisted of 3 sets of 6 repetitions, with an inertial load of 0.029 kg.m2. Isokinetic quadriceps (knee extension) and hamstrings (knee flexion) concentric peak torque (60º/s) and hamstring eccentric peak torque (-60º/s) were measured 5min after experimental or control conditions. A significant condition (PAPE) effect was reported (f =4.067, p =0.008) for isokinetic hamstrings eccentric peak torque following FW-squat and FW-deadlift, but no significant differences were found for quadriceps and hamstrings concentric peak torques. The significant difference averaged 14Nm between FW-squat vs. control (95% CI: 2, 28; d =0.75, moderate; p =0.033), and 13Nm between FW-deadlift vs. control (95% CI: 1, 25; d =0.68, moderate; p =0.038). This study reported that both FW-squat and FW-deadlift exercises are equivalently capable of generating PAPE of isokinetic hamstrings eccentric torque. Practitioners may use these findings to inform strength and power development during complex training sessions consisting of flywheel-based exercises prior to a sport-specific task.